2011
DOI: 10.1016/j.semcancer.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Emerging importance of ALK in neuroblastoma

Abstract: Since the original descriptions of gain-of function mutations in anaplastic lymphoma kinase (ALK), interest in the role of this receptor tyrosine kinase in neuroblastoma development and as a potential therapeutic target has escalated. As a group, the activating point mutations in full-length ALK, found in approximately 8% of all neuroblastoma tumors, are distributed evenly across different clinical stages. However, the most frequent somatic mutation, F1174L, is associated with amplification of the MYCN oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 73 publications
(164 reference statements)
0
81
0
2
Order By: Relevance
“…4), extramedullary plasmacytoma (5), renal cell carcinoma (6), thyroid cancer (7), basal cell carcinoma (8), breast cancer, and colorectal cancer (9,10). Moreover, aberrant activation or overexpression of full-length ALK has an oncogenic role in neuroblastoma (11,12) and glioblastoma multiforme (13,14). The oncogenic properties of aberrantly activated ALK are mainly due to the deregulated activation of different downstream pathways such as RAS/ RAF/MEK/ERK1/2 and PCLg, involved in cellular proliferation, and PI3K/AKT and JAK3/STAT3, that promote cell survival (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…4), extramedullary plasmacytoma (5), renal cell carcinoma (6), thyroid cancer (7), basal cell carcinoma (8), breast cancer, and colorectal cancer (9,10). Moreover, aberrant activation or overexpression of full-length ALK has an oncogenic role in neuroblastoma (11,12) and glioblastoma multiforme (13,14). The oncogenic properties of aberrantly activated ALK are mainly due to the deregulated activation of different downstream pathways such as RAS/ RAF/MEK/ERK1/2 and PCLg, involved in cellular proliferation, and PI3K/AKT and JAK3/STAT3, that promote cell survival (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research work from our laboratory and others has identified activating mutations in the tyrosine kinase domain of the ALK transmembrane receptor tyrosine kinase, which are found in the majority of hereditary neuroblastoma and occur as somatic defects in 7% to 10% of sporadic cases (3)(4)(5)(6). During embryonic development, ALK is expressed in the central and peripheral nervous system (7), where it may regulate the interplay between cell proliferation and differentiation of the developing sympatho-adrenal cells of the neural crest (1, 8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It is an oral small-molecule tyrosine kinase inhibitor, originally developed as a c-MET inhibitor and later found an inhibitor for ALK phosphorylation [30,31]. In vitro studies demonstrated that crizotinib is potent in neuroblastoma cell lines with ALK amplification or the R1275Q mutation, one of the most common ALK variants in neuroblastoma [32]. Whereas cells bearing ALKF1174L mutation are relatively crizotinib-resistant [18,19,33,34].…”
Section: Alk Targeted Agents In Neuroblastomamentioning
confidence: 99%